Rangkap Jabatan Kepala Sekolah Dan Pengaruhnya Terhadap Manajemen Sekolah Dasar: Studi Kasus Di Kota Cirebon - Zidane Ardiansyah; Julia Julia; Cucun Sunaengsih (Elementary Teacher Education Program, Majalengka University, 2023)
The rise of school principals with multiple positions in Indonesia raises concerns about the quality of the schools they lead, especially their duties as school managers. This study aims to find out cases of dual school principals and their effects on elementary school management. This study uses a qualitative method with multiple case study designs. Data collection used an open interview instrument with 4 school principals with multiple positions in Cirebon City, West Java. The research questions will include (1) Why do cases of multiple positions occur? (2) What are the duties of the school principal with multiple positions? (3) What is the influence of the multi-position school principal on elementary school management? As for the data analysis used is thematic analysis. The results showed that school principals with multiple positions occurred because there was no replacement principal when the previous principal died or retired so that another principal was used as a temporary replacement. This substitute principal continues to carry out his duties as a normal principal. However, with this double burden, substitute principals experience physical and mental fatigue, thereby reducing work effectiveness, besides that there is no significant effect on school principals who hold concurrent positions on the quality of school management. With this research, it is hoped that it will be able to become a new point of view regarding school principals with multiple positions in Indonesia.